Introducing KPK and FPB Material Using Pahima Media (Mathematics Counting Board) for Grade V Students in Elementary School - Amin, Muhammad; Jamilah, Ika Imroatul (Journal of Insan Mulia Education, 2024)
The aims of this research are: 1) to describe learning constraints; 2) to describe the initial didactic design; 3) to describe learning activities when using the initial didactic design; 4) to describe the final design of the didactic material for learning mathematics from KPK and FPB. For the purpose of this investigation, a method known as Didactic Design Research (DDR) was used to conduct qualitative research. Data collection used interview methods, tests, documentation, and video recordings. The didactic design research process has several stages, which are 1) Pedagogical Didactic Anticipation (ADP) Analysis, 2) Metapedagogical analysis, which is the second choice, and 3) Past examination. Students showed various responses during their education, as shown by the investigation findings. Even though learning can take a short time, through the use of Pahima media, students can understand and enjoy learning about FPB and KPK. Therefore, in the final didactic design, there are improvements that emphasize the practice questions that have been provided more, and as a consequence, the researcher made modifications to these questions. At the beginning of the lesson, there were two questions that students had not completed correctly. This collection of questions was based on the idea of ​​​​LCM and FPB as a fairy tale, with the first and second questions discussing different story questions from the examples explained earlier. Children could not understand these components as a whole.